THE EFFECT OF MATERIALISM AND FINANCIAL KNOWLEDGE ON FINANCIAL STRESS: THE ROLE OF PRESENT FATALISTIC AND MARITAL STATUS - Lutfi, Lutfi; Firdaus, Dimas Gita Ramadhan; Dwiyanti, Elicia Aprillia; Dela Renta, Yolanda (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The conditions of the Covid 19 outbreak during 2019 and 2020 made some people lose their jobs or income, which resulted in increased financial pressures. This research examines the influence of present fatalistic, materialism, financial knowledge, and marital status on financial stress. Data were collected using a questionnaire. The number of samples that can be processed in the study was 484 respondents. The analysis technique used is the partial least squares structural equation modeling (PLS-SEM). The direct test results show that present fatalistic and materialism significantly increase financial stress, while financial knowledge and marital status reduce financial stress. Present fatalistic has been shown to positively mediate materialism's effect on financial stress. Meanwhile, marital status strengthens the negative influence of financial knowledge on financial pressure. It means that marital status encourages someone with good financial knowledge to use their ability to manage their finances to avoid financial stress. This study recommends to the public the importance of controlling materialistic behavior, reducing hopelessness, and increasing self-control to reduce financial pressureJEL : D12, D14.ABSTRAKKondisi wabah Covid 19 selama tahun 2019 dan 2020 membuat sebagian masyarakat kehilangan pekerjaan atau penghasilannya, yang mengakibatkan tekanan keuangan semakin meningkat. Penelitian ini menguji pengaruh fatalistik masa kini, materialisme, pengetahuan keuangan, dan status perkawinan terhadap tekanan keuangan. Pemilihan sampel didasarkan pada metode purposive sampling, dan pengumpulan data dilakukan dengan menggunakan kuesioner. Jumlah sampel yang dapat diolah adalah 484 responden. Teknik analisis yang digunakan adalah Partial Least Square Structural Equation Modeling (PLS-SEM). Hasil pengujian pengaruh langsung menunjukkan bahwa fatalistik masa kini dan materialisme secara signifikan meningkatkan tekanan keuangan, sedangkan pengetahuan keuangan dan status perkawinan mengurangi tekanan keuangan. Fatalistik masa kini terbukti secara positif memediasi pengaruh materialisme pada tekanan keuangan. Sementara itu, status perkawinan memperkuat pengaruh negatif pengetahuan keuangan terhadap tekanan keuangan. Hal ini berarti bahwa status perkawinan mendorong seseorang yang memiliki pengetahuan keuangan yang baik untuk menggunakan pengetahuan tersebut dalam mengelola keuangannya agar terhindar dari tekanan keuangan. Studi ini merekomendasikan kepada masyarakat pentingnya mengendalikan perilaku materialistis, mengurangi keputusasaan, dan meningkatkan pengendalian diri untuk mengurangi tekanan keuangan.Kata Kunci : tekanan keuangan, materialisme, pengetahuan keuangan, fatalistik masa kini, status perkawinan.